Dolosigranulum pigrum modulates immunity against SARS-CoV-2 in respiratory epithelial cells - Islam, Md Aminul (2021)
In a previous work, we demonstrated that nasally administered Dolosigranulum pigrum 040417 beneficially modulated the respiratory innate immune response triggered by the activation of Toll-like receptor 3 (TLR3) and improved protection against Respiratory Syncytial Virus (RSV) in mice. In this work, we aimed to evaluate the immunomodulatory effects of D. pigrum 040417 in human respiratory epithelial cells and the potential ability of this immunobiotic bacterium to in-crease the protection against Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The respiratory commensal bacterium D. pigrum 040417 differentially modulated the production of IFN-β, IL-6, CXCL8, CCL5 and CXCL10 in the culture supernatants of Calu-3 cells stimulated with poly(I:C) or challenged with SARS-CoV-2. The differential cytokine profile induced by the 040417 strain was associated with a significant reduction in viral replication and cellular damage after coronavirus infection. Of note, D. pigrum 030918 was not able to modify the resistance of Calu-3 cells to SARS-CoV-2 infection, indicating a strain-specific immunomodulatory effect for respiratory commensal bacteria. The findings of this work improve our understanding of the immunological mechanisms involved in the modulation of respiratory immunity induced by respiratory commensal bacteria, by demonstrating their specific effect on respiratory epithelial cells. In addition, the results suggest that particular strains such as D. pigrum 040417 could be used as a promising alternative for combating SARS-CoV-2 and reducing the severity of COVID-19.